A detailed palaeomagnetic study of the oldest (≈15 Myr) lava sequences in Northwest Iceland (Dataset) ... - Kristjansson, Leo; Hardarson, Björn S.; Audunsson, Haraldur (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: A detailed palaeomagnetic study of the oldest (≈15 Myr) lava sequences in Northwest Iceland ...